ASSESSMENT OF POSTOPERATIVE PAIN LEVEL IN HEMORRHOIDS, ANAL FISSURE, PARAPROCTITIS AND PARARECTAL FISTULA (Proceedings of International Educators Conference, 2023)
The pain after proctological operations is the strongest because the injury is in the anal area and is associated with defecation. Postoperative pain depends on the type of disease, its degree, the type of operation, the type of anesthesia, the surgeon's skills, and the patient's individual sensitivity.